English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a. log(x-4)=3
b. log3(2-x)=3

2006-12-06 09:42:17 · 5 answers · asked by Katy J 1 in Science & Mathematics Mathematics

5 answers

a) 10^3=x-4
x=1000+4=1004

b) l0^3=3(2-x)
10^3=6-3x
3x=6-1000=-994
x= - 331 1/3

2006-12-06 09:51:42 · answer #1 · answered by captain173 2 · 0 0

For part a:

log(x-4) = 3

"Think 10 to the both sides"

So,

10^(log(x-4)) = 10^3

(x-4) = 1000
x = 1004


For part b, just think "3 to the both sides [if it's a base 3 log, not sure if that was multiplication]"

log3(2-x) = 3

3^(log3(2-x)) = 3^3

2-x = 27

-x = 25

x = -25

2006-12-06 18:00:28 · answer #2 · answered by Mark D 1 · 0 0

a. log(x-4)=3
take the inverse log of both sides & solve for x
(x-4)=10^3 =1000
x-4+4 =1000+4
x=1004

b. log3(2-x)=3 (is this log base 3 or log base 10?)

if base 3
log3(2-x)=3
take the inverse log
2-x = 3^3 =27
-x = 27-2 =25
x=-25

2006-12-06 18:10:41 · answer #3 · answered by rm 3 · 0 0

General advice: Practice how to convert from logarithmic form to exponential form.

For part (a), if there is no given base, then the default is base 10. Steps to convert to exponential form are as follows:
(1) The base of the log becomes the base of the exponent.
(2) The inside of the log becomes the answer.

Therefore, if we take log(x-4) = 3
The base of the log (10) is the base of the exponent.
The inside of the log (x-4) is the answer.
(What's remaining becomes the expontent)

10^3 = x - 4
1000 = x-4
x = 996

Try part b that way.

2006-12-06 18:05:50 · answer #4 · answered by Puggy 7 · 0 0

b. 3^3=2-x
x=2-9
x=-7

2006-12-06 17:52:46 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers